The Nexus of Gender Inequality and Poverty Rate in Indonesia - Muhammad, Fadhal (Perspektif : Jurnal Ekonomi dan Manajemen Akademi Bina Sarana Informatika, 2024)
The phenomenon of feminization of poverty intertwines issues of poverty and gender as interconnected challenges. This research aims to elucidate the intricate relationship between gender inequality and the poverty rate in Indonesia, utilizing panel data from 34 provinces during 2018 to 2022. Multiple linear regression modeling is used to analyze the impact of independent variables comprising the Gender Inequality Index (GII), Gender Development Index (GDI), Gender Empowerment Index (GEI), dependency ratio, and Gini ratio on the poverty rate. The findings reveal that GII, GEI, dependency ratio, and Gini ratio significantly positively affect the poverty rate, while GDI significantly negatively affects the poverty rate. Consequently, comprehensive and gender-aware policies are essential to alleviate gender inequality and poverty issues.